Multiomics reveals the synergistic response of gut microbiota and spider A. ventricosus to lead and cadmium toxicity - Chen, Jinkun; Liu, Jing; Liu, Shize; Li, Zhongyuan; Gao, Cuimei; Wang, Zhuoman; Huang, Siqi; Jiang, Zijian; Yang, Huilin (Bulletin of environmental contamination and toxicology, 2025)
The potential crosstalk between the host and gut microbiota (GM) under heavy metal compound pollution remains unexplored. Herein, using comprehensive analysis of metagenomics, metabolomics, behavioral analysis, and cell morphology to investigate the causal relationship between GM and host responses to cadmium (Cd) and lead (Pb) toxicities. Results indicate that Pb and Cd pollution, alone or together, hinder spider predatory behavior and change the composition and function of GM. Combined exposure reduces protein and exogenous compound metabolism, while single exposure affects energy and lipid metabolism. Gut microbiota helps spider antioxidant activity by increasing glutathione, lipoic acid, and L-cysteine. Oxidative damage, increased Enterobacteriaceae (Salmonella), and lipopolysaccharide (LPS) may harm the midgut barrier. Upregulation of choline and acetylcholine, and downregulation of spermidine, may initiate neurotoxicity. Inhibiting actinomycetes might boost sodium gallate for detoxifying single contaminants. Combined pollution detoxification may involve downregulation of indole synthesis metabolic bacteria, tryptophan, indole metabolites, cytochrome P450 (CYP450), and an increase in Desulfobulbia could remove heavy metals and reduce oxidative stress. Combined pollution has a synergistic effect, making the toxicity of multiple pollutants greater than their individual effects, impacting metal resistance genes (MRGs), and antibiotic resistance ontology (AROs) which used for classifying and describing antibiotic resistance, midgut barrier integrity, oxidative stress, and detoxification. The results help to elucidate the interplay of GM and host's reactions, and aid in monitoring and bioremediation of heavy metal pollution.